The Effectiveness of Using Smartphones in Distance Learning During the Covid-19 Pandemic - Ilham Ilham (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to describe and analyze the effectiveness of using smartphones in distance learning during the Covid-19 pandemic at MAS Al-Washliyah, Tanjung Tiram District, Batubara Regency. This study uses a qualitative approach with a descriptive study method. Data was collected through participatory observation techniques, in-depth interviews, and document review. The results of this study concluded that the use of smartphones in the learning process at MAS Al-Washliyah during the Covid-19 pandemic was very ineffective. This is indicated by (1) students do not understand the material taught by the teacher, due to network constraints (internet connection), (2) students do not take lessons seriously, with student behavior that seems bored, sleepy, and bored with online learning, (3) the character of students who are not fully controlled in the learning process, even opening other applications while learning, such as Facebook, Instagram, tik tok, chatting via WhatsApp, and playing online games. The implications of using smartphones in the online learning process are (1) positive impacts, including breaking the chain of Covid-19 spread, students are closer to their families, students view learning as not limited to school but at home or other places; (2) negative impacts, including learning is just a formality and students do not understand the teaching material.